2009
DOI: 10.1016/s0377-1237(09)80089-0
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Versus Endoscopic Powered Adenoidectomy: A Comparative Study

Abstract: Endoscopic powered adenoidectomy was found to be a safe and effective tool for adenoidectomy. The study parameters where endoscopic powered adenoidectomy fared better were completeness of resection, accurate resection under vision, lesser collateral damage and faster recovery time. On the other hand, conventional adenoidectomy scored in matter of lesser operative time and intra-operative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 10 publications
4
40
0
Order By: Relevance
“…In our study 10% (3) cases in the conventional group had Eustachian tube damage and no collateral damage in endoscopic group. A study by Datta et al 34 in 2009 yielded similar results 5 cases in group A had posterior septal wall or vault region injury and 3 cases had injury to torus tubaris. One case in endocopic group in this study had injury to nasal mucosa whereas in our study the endoscopic group showed no mucosal injuries (graph-2).…”
Section: Section: Entmentioning
confidence: 63%
See 1 more Smart Citation
“…In our study 10% (3) cases in the conventional group had Eustachian tube damage and no collateral damage in endoscopic group. A study by Datta et al 34 in 2009 yielded similar results 5 cases in group A had posterior septal wall or vault region injury and 3 cases had injury to torus tubaris. One case in endocopic group in this study had injury to nasal mucosa whereas in our study the endoscopic group showed no mucosal injuries (graph-2).…”
Section: Section: Entmentioning
confidence: 63%
“…This result is comparable to the results of study by Hussein and Al-juboori S et al in 2012. 32 And also studies by stansilaw et al 33 , Havas et al 22 , Datta et al 34 and Ezzat et al 35 with an incidence of 20%, 39%, 39%, 30% and 14.5% residual tissue respectively. In the study by V Anand et al 31 in 2013 in Amritsar also showed 25% residual adenoid in conventional group and complete removal in the endoscopic group.…”
Section: Section: Entmentioning
confidence: 88%
“…In another study done by Datta et al, they stated that Endoscopic powered adenoidectomy was found to be a safe and effective tool for adenoidectomy. 8 The study parameters where endoscopic powered adenoidectomy fared better were completeness of resection, accurate resection under vision, lesser collateral damage and faster recovery time. On the other hand, conventional adenoidectomy scored in matter of lesser operative time and intra-operative bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…The former technique of adenoidectomy ensures complete tissue removal and reduced operative duration but has the disadvantage of increased intraoperative bleeding. 12 Coblation is associated with reduced blood loss and complete tissue removal but the equipment is expensive. When compared with coblation and microdebrider, suction diathermy is less expensive.…”
Section: Discussionmentioning
confidence: 99%